A QM/MM Investigation of the Catalytic Mechanism of Metal-Ion-Independent Core 2 β1,6-N-Acetylglucosaminyltransferase - Tvaroška, Igor; Kozmon, Stanislav; Wimmerová, Michaela; Koča, Jaroslav (Chemistry : a European journal, 2013)
β1,6‐GlcNAc‐transferase (C2GnT) is an important controlling factor of biological functions for many glycoproteins and its activity has been found to be altered in breast, colon, and lung cancer cells, in leukemia cells, in the lymhomonocytes of multiple sclerosis patients, leukocytes from diabetes patients, and in conditions causing an immune deficiency. The result of the action of C2GnT is the core 2 structure that is essential for the further elongation of the carbohydrate chains of O‐glycans. The catalytic mechanism of this metal‐ion‐independent glycosyltransferase is of paramount importance and is investigated here by using quantum mechanical (QM) (density functional theory (DFT))/molecular modeling (MM) methods with different levels of theory. The structural model of the reaction site used in this report is based on the crystal structures of C2GnT. The entire enzyme–substrate system was subdivided into two different subsystems: the QM subsystem containing 206 atoms and the MM region containing 5914 atoms. Three predefined reaction coordinates were employed to investigate the catalytic mechanism. The calculated potential energy surfaces discovered the existence of a concerted SN2‐like mechanism. In this mechanism, a nucleophilic attack by O6 facilitated by proton transfer to the catalytic base and the separation of the leaving group all occur almost simultaneously. The transition state for the proposed reaction mechanism at the M06‐2X/6‐31G** (with diffuse functions on the O1′, O5′, OGlu, and O6 atoms) level was located at C1O6=1.74 Å and C1O1=2.86 Å. The activation energy for this mechanism was estimated to be between 20 and 29 kcal mol−1, depending on the method used. These calculations also identified a low‐barrier hydrogen bond between the nucleophile O6H and the catalytic base Glu320, and a hydrogen bond between the N‐acetamino group and the glycosidic oxygen of the donor in the TS. It is proposed that these interactions contribute to a stabilization of TS and participate in the catalytic mechanism. A model subject: The catalytic mechanism of the key enzyme in the biosynthesis of branched O‐glycans, the metal‐ion‐independent β1,6‐GlcNAc‐transferase (C2GnT), was investigated by using quantum mechanical (QM) (density functional theory)/molecular modeling (MM) methods (see figure).